2017
DOI: 10.1080/00952990.2017.1314489
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2*2 and peer drinking in East Asian college students

Abstract: Background: The ALDH2*2 allele (A-allele) at rs671 is more commonly carried by Asians and is associated with alcohol-related flushing, a strong adverse reaction to alcohol that is protective against drinking. Social factors, such as having friends who binge drink, also contribute to drinking in Asian youth. Objectives: This study examined the interplay between ALDH2*2, peer drinking, and alcohol consumption in college students. We hypothesized that the relationship between ALDH2*2 and standard grams of ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…College students are particularly susceptible to the influence of peers and social norms related to alcohol and substance use due to increased autonomy by leaving home and the pressure to fit in new social networks (Arnett, 2005). There is evidence from both latent (e.g., twin studies) and measured genetic studies that genetic effects on alcohol use outcomes are greater when peer deviance is high, for both adolescents (Cooke et al, 2015; Dick & Kendler, 2012) and young adults, including college students (O'Shea et al, 2017; Poelen, Scholte, Willemsen, Boomsma, & Engels, 2007). Some studies indicated that peer influence on alcohol outcomes varied as a function of individuals’ genetic predisposition.…”
Section: G × E: the Role Of Peer Deviance And Interpersonal Traumaticmentioning
confidence: 99%
“…College students are particularly susceptible to the influence of peers and social norms related to alcohol and substance use due to increased autonomy by leaving home and the pressure to fit in new social networks (Arnett, 2005). There is evidence from both latent (e.g., twin studies) and measured genetic studies that genetic effects on alcohol use outcomes are greater when peer deviance is high, for both adolescents (Cooke et al, 2015; Dick & Kendler, 2012) and young adults, including college students (O'Shea et al, 2017; Poelen, Scholte, Willemsen, Boomsma, & Engels, 2007). Some studies indicated that peer influence on alcohol outcomes varied as a function of individuals’ genetic predisposition.…”
Section: G × E: the Role Of Peer Deviance And Interpersonal Traumaticmentioning
confidence: 99%
“…The signi cant association between the decreased risk of alcohol dependence and ALDH2*2 has been shown in many Asian studies [23,26] including a meta-analysis that demonstrated the link between ALDH2*1 and increased risk of AD according to a dominant model only in east Asians. O'Shea et al analyzed the relationship between ALDH2*2 A allele and peer drinking in east Asian college students con rming the strong protective effect of ALDH2*2 against alcohol addiction [32]. In an Indian study though, in contrast to studies on Asian subjects, Vaswani et al found a high frequency of ALDH2*2 among north Indian alcohol dependent subjects and deemed it to be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies could examine level of peer drinking and whether Asian students are U.S. born, which are also associated with greater alcohol consumption. 5,21…”
Section: Limitationsmentioning
confidence: 99%
“…3 Studies show that these discomforts are not always enough to prevent risky alcohol consumption among individuals who experience alcohol-related flushing, including college students. [4][5][6] The result for those who continue to drink despite experiencing facial flushing is an increased exposure to acetaldehyde and the associated risk for serious health consequences. Even light drinking, for individuals who carry the ALDH2*2 genetic marker, is associated with a higher risk for head and neck cancers.…”
mentioning
confidence: 99%